Analisis Pengaruh Kombinasi Bisnis Merger bagi PT Gojek Indonesia (Jurnal Kendali Akuntansi, 2024)
This research aims to analyze the business combination of the merger between the companies Gojek and Tokopedia to become PT GoTo. This research uses a descriptive method by applying literature reviews from previous research. The data used uses secondary data. The data obtained is then processed by relating the issue of the influence of business combinations in PT. GoTo with references and other real sources. The objects of this research are the Gojek and Tokopedia companies. The results of the analysis obtained are that GoTo is the largest technology-based company in Indonesia. The conclusion obtained is that PT GoTo can provide platform services for customers and employees to be more advanced